CounterAKTing HIV: Toward a “Block and Clear” Strategy? - Pasquereau, Sébastien; Herbein, Georges (Frontiers in Cellular and Infection Microbiology, 2022)
The protein kinase B or Akt is a central regulator of survival, metabolism, growth and proliferation of the cells and is known to be targeted by various viral pathogens, including HIV-1. The central role of Akt makes it a critical player in HIV-1 pathogenesis, notably by affecting viral entry, latency and reactivation, cell survival, viral spread and immune response to the infection. Several HIV proteins activate the PI3K/Akt pathway, to fuel the progression of the infection. Targeting Akt could help control HIV-1 entry, viral latency/replication, cell survival of infected cells, HIV spread from cell-to-cell, and the immune microenvironment which could ultimately allow to curtail the size of the HIV reservoir. Beside the “shock and kill” and “block and lock” strategies, the use of Akt inhibitors in combination with latency inducing agents, could favor the clearance of infected cells and be part of new therapeutic strategies with the goal to “block and clear” HIV.